2008
DOI: 10.1016/j.annemergmed.2008.06.047
|View full text |Cite
|
Sign up to set email alerts
|

133: Rapid Sequence Intubation From the Patients' Perspective

Abstract: This study assesses the efficacy of the rapid sequence intubation (RSI) protocol in preventing patient recollection of resuscitative events and patient discomfort during intubation, as subjectively determined by the patient. Methods: This was a prospective study of all patients intubated at Los Angeles County, University of Southern California Medical Center from July 2009 to January 2010. Extubated patients were interviewed using a standard questionnaire and data collection tool. Results: Of 211 airway codes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…On the other extreme, under-dosing is a concern if ideal body weight (IBW) is inappropriately used for weight-based dosing regimens, since the calculation for IBW only considers height and not excess weight. This is particularly relevant for patients who receive etomidate prior to neuromuscular blocker therapy as under-dosing may lead an awake state during paralysis [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other extreme, under-dosing is a concern if ideal body weight (IBW) is inappropriately used for weight-based dosing regimens, since the calculation for IBW only considers height and not excess weight. This is particularly relevant for patients who receive etomidate prior to neuromuscular blocker therapy as under-dosing may lead an awake state during paralysis [5].…”
Section: Methodsmentioning
confidence: 99%
“…In light of etomidate's large volume of distribution, there is a concern of under-dosing in more obese patients, which could lead to patient awareness during concomitant paralysis with a neuromuscular blocker [62]. In one prospective study evaluating an RSI protocol, 5 of the 10 patients interviewed remembered aspects of the intubation procedure suggesting inadequate sedation [5]. Concerns of inadequate dosing would outweigh toxicity concerns of higher doses based on ABW in most obese patients.…”
Section: Etomidatementioning
confidence: 99%
“…12 In reality, intubation can inflict a great deal of suffering on patients. 16 In a situation where a treating physician believes intubation will not likely provide survival benefits to a terminal patient, the physician would feel ethically uneasy to intubate the patient just to satisfy the demands of the family. Although EPs strive to do the ''right thing'' for dying terminal patients (e.g., allow natural death), not intubating and going against family's demands has the potential for negative consequences, from a simple complaint affecting satisfaction scores to a potential malpractice suit.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the ED domain are even more limited. Four small studies (n=123 patients total) showed an incidence of awareness with paralysis ranging from 5.9% to 50%,20–23 but this was restricted to the endotracheal intubation procedure only. One small cohort study showed no association between BIS values and recall of endotracheal intubation in the ED 21…”
Section: Introductionmentioning
confidence: 99%